Trabajo doméstico y migraciones latinoamericanas. Desde Argentina, hallazgos y reflexiones frente a los destinos extrarregionales - Rosas, Carolina; Jaramillo Fonnegra, Verónica; Blas Vergara, Albano (El Colegio de México A.C., 2015)
In order to contribute to the debate on the participation of migrant women in paid domestic work, the aim of this article is to analyze two aspects in which Argentina (the main intraregional destination) contrasts with the United States and Spain (main extra-regional destinations). The survey is analyzed to study the composition of the domestic sector in the last decade according to the employees’ migratory status; a legal analysis is subsequently used to describe the laws regulating this employment relationship. The main findings include the fact that the domestic work sector is mainly comprised of non-migrant Argentine women and that it is becoming less dependent on internal migrant labor. Unlike what happens in extra-regional destinations, the sector does not rely on foreign labor. The paper also shows that the composition varies by region/agglomeration considered. Lastly, it observes that the three countries have made legislative progress in recent years, and that in specific aspects, Argentine law provides the greatest protection.